2005
DOI: 10.4025/actascianimsci.v27i2.1233
|View full text |Cite
|
Sign up to set email alerts
|

Estratégia alimentar para dieta baseada em palma forrageira sobre o desempenho e digestibilidade em vacas em final de lactação

Abstract: Estratégia alimentar para dieta baseada em palma forrageira sobre Estratégia alimentar para dieta baseada em palma forrageira sobre Estratégia alimentar para dieta baseada em palma forrageira sobre Estratégia alimentar para dieta baseada em palma forrageira sobre o desempenho e digestibilidade em vacas em RESUMO. Para avaliar os efeitos de diferentes estratégias alimentares em dietas à base de palma forrageira no desempenho de vacas da raça holandesa em lactação, foram utilizados cinco animais com 230 dias de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…Para estimativa dos CT, foi utilizada equação proposta por Sniffen et al (1992), CT = 100 -(%PB + %EE + %cinzas) e, para estimativa dos CNF, adotou-se a equação descrita por Hall (2001), em que CNF = 100% -(PB% + FDN% -FDNpb + EE% + Cinzas%) e FDNpb é a proteína bruta insolúvel em detergente neutro. Os nutrientes digestíveis totais (NDT) foram calculados pela equação: NDT = PBd + CTd + 2,25 (EEd), de acordo com Sniffen et al (1992).…”
Section: Introductionunclassified
“…Para estimativa dos CT, foi utilizada equação proposta por Sniffen et al (1992), CT = 100 -(%PB + %EE + %cinzas) e, para estimativa dos CNF, adotou-se a equação descrita por Hall (2001), em que CNF = 100% -(PB% + FDN% -FDNpb + EE% + Cinzas%) e FDNpb é a proteína bruta insolúvel em detergente neutro. Os nutrientes digestíveis totais (NDT) foram calculados pela equação: NDT = PBd + CTd + 2,25 (EEd), de acordo com Sniffen et al (1992).…”
Section: Introductionunclassified
“…According to Pessoa et al (2004) there was an imbalance between the supplied and the consumed diet in the treatment with separate ingredients. The feeding strategy based on TMR prevents, among other factors, food selection, and consequently excessive consumption of any ingredient in the diet (Van Soest, 1994;Nocek, 1997;NRC, 2001;Ingvarsten et al, 2001;Silva et al, 2005) a fact which was not observed in this study, where it was verified effect of selectivity in the proportion of nutrients effectively consumed in relation to the nutrients in the offered diet, even in the form of total mixed ration supply.…”
Section: Results E Discussionmentioning
confidence: 52%
“…These data are inn accordance to Davenport et al (1983) and Nocek et al (1986), who found no significant differences in milk production when comparing the effect of total mixed ration and separate concentrate feeding strategies on the performance of dairy cows. Silva et al (2005) assessing different feeding strategies with cactus-based diets for Holstein cows, found no differences between total mixed rations and separate concentrate feeding strategies on milk production and composition.…”
Section: Results E Discussionmentioning
confidence: 98%